Morbidity and mortality associated with atherosclerotic peripheral artery disease: A systematic review. (January 2020) - Agnelli, Giancarlo; Belch, Jill J.F.; Baumgartner, Iris; Giovas, Periklis; Hoffmann, Ulrich
Abstract: Background and aims: It is unclear whether improvements in the detection/treatment of peripheral artery disease (PAD) affect overall survival and morbidity. We undertook a systematic review to describe survival and morbidity in contemporary PAD cohorts. Methods: Electronic databases were searched for randomised and observational studies reporting mortality/morbidity events between 1 May 2003 and 31 December, 2017 in patients with PAD, diagnosed by intermittent claudication (IC), critical limb ischaemia (CLI), or an ankle brachial index (ABI) < 0.9. Pooled event rates for all-cause and cardiovascular (CV) mortality, non-fatal myocardial infarction (MI), non-fatal stroke, major CV events (MACE; non-fatal MI/stroke, CV death), and major amputation were calculated per 1000 person-years. Results: 124 eligible studies were identified (570, 856 patients; 855, 894 person-years of follow-up). Statin use was reported in 67% of the overall cohort and antiplatelet use in 79%. Pooled event rates for all-cause and CV mortality, MI, stroke, MACE, and major amputation were 113, 39, 20, 12, 71, and 70 per 1000 person-years, respectively. Compared with patients with an ABI <0.9, the presence of CLI was associated with increased rates of all-cause and CV mortality, MI, MACE, and major amputation. Event rates for stroke were similar between patients with an ABI <0.9 and CLI. Conclusions: Our data show PAD patients have a high risk of all-cause and CV mortality, and imply the risk of stroke or MI is at least equivalent to the risk in patients with coronary artery disease. Moreover, our data underline the need for improved treatments to attenuate CV risk in PAD patients. Graphical abstract: Image 1 Highlights: PAD patients have a high risk of all-cause and cardiovascular (CV) mortality. Patients with critical limb ischaemia were at highest risk ( versus ABI <0.9). Fewer patients with critical limb ischaemia received statins ( versus ABI <0.9). The risk of stroke or MI is at least equivalent to that of coronary artery disease. Improved treatments are needed to attenuate CV risk in PAD patients.